The logistics service providers’ capabilities, the government administration, resources and competitive advantage to the performance of the operational cross-border logistics between Thailand and Malaysia - Pengman, Hasamon (2022)
The economic growth of countries with shared borders primarily relies on effective cross-border logistics operations as accelerated by the relevant parties. Therefore, it is pertinent to investigate the performance of the operational cross-border logistics (POCL) between Thailand and Malaysia, where operational limitations could be resolved. This covers the relationships between government administration (GA), logistics service providers’ capabilities (LSPC), resources (R), competitive advantage (CA) and POCL. There is also a need to ascertain whether GA, LSPC and CA mediate these relationships grounded upon the Global Value Chains (GVCs), Resources-Based View (RBV) and Competitive Advantage (CA) theories. Data was collected from 181 logistics enterprise employees in both countries. All the constructs were processed quantitatively using the Partial Least Squares Structural Equation Modeling (PLS-SEM). The Smart PLS V3 and SPSS V21 were used for data analysis. The findings indicate that R has a positive effect on LSPC, CA and GA, whilst POCL is influenced by GA, LSPC and CA. LSPC has a significant effect on CA, whilst GA has a no significant effect on CA. In addition, GA, CA and LSPC act as significant mediators in the relationship between R and POCL. These results provide straightforward recommendations for enhancing POCL which highlight the important roles of LSPC in service and innovation capabilities, and GA in trust and reliability for cross-border operations. In terms of resources, the focus is on how resources can be properly managed to achieve more effective operations for cross-border logistics. The findings have theoretical implications on the GVCs, RBV and CA integrated in the model, given the approaches to minimize complexities with maximum value for the operations, and recommend unique strategies for providing high quality services with competitive prices. The study supports the context of cross-border logistics which is applicable for achieving high POCL in the current circumstance.